Comparing and Contrasting Quality Frameworks Using Research on High-Probability Requests With Young Children. Issue 4 (October 2022) - Hardy, Jessica K.; McLeod, Ragan H.; Sweigart, Chris A.; Landrum, Timothy
Abstract : The purpose of this study was to compare and contrast frameworks for evaluating methodological rigor in single case research. Specifically, research on high-probability requests to increase compliance in young children was evaluated. Ten studies were identified and were coded using 4 frameworks. These frameworks were the Council for Exceptional Children Standards for Evidence-based Practices, What Works Clearinghouse, Risk of Bias Assessment for Single Subject Experimental Designs, and Single Case Analysis and Review Framework. Significant differences were found across frameworks, both in the rating of rigor and the study effects. Implications for determining high-quality research and effective practices are discussed.